Integrative model for the selection of a new product launch strategy, based on ANP, TOPSIS and MCGP: a case study - Liao, Chin-Nung; Lin, Chih-Hsiang; Fu, Yan-Kai (Technological and Economic Development of Economy, 2016)
New product launch strategy is a key competitive advantage for a new product development. A new product launch is a multiple criteria decision-making problem, which involves evaluating different criteria or attributes in a strategy selection process. The purpose of this paper is to develop a qualitative and quantitative approach for the selection of a new product launch strategy. The current study proposes an integrated approach, integrating analytic network process, the technique for order preference by similarity to an ideal solution and multi-choice goal programming, which can be used to determine the best launch strategy for marketing problems. The advantage of this integrated method is that it enables the consideration of both tangible (qualitative) and intangible (quantitative) criteria as well as both “more/higher is better” (e.g., benefit criteria) and “less/lower is better” (e.g., cost criteria) in the launch strategy of a new product selection problem. To show the practicality and usefulness of this method, an empirical example of a watch company is demonstrated. First published online: 03 Nov 2015